2015
DOI: 10.5152/akd.2014.5217
|View full text |Cite
|
Sign up to set email alerts
|

Left atrial dyssynchrony time measured by tissue Doppler imaging to predict atrial fibrillation recurrences after pulmonary vein isolation

Abstract: Objective:In this study we assess the value of left atrial dyssynchrony time measured by tissue Doppler imaging (TDI) to predict recurrences after pulmonary vein isolation (PVI) in patients with paroxysmal and persistent atrial fibrillation (AF).Methods:One hundred sixty patients (57±7.5 years, 122 males) with symptomatic drug-refractory paroxysmal and persistent AF, undergoing PVI were enrolled in our study. PA peak time by tissue Doppler imaging (PApeak-TDI) is defined as the time measured from the start of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…to be predictors of the occurrence or recurrence of AF, [9][10][11][12][13][14][15][16][17] some other investigators have regarded them as early markers of LA structural remodeling. [44][45][46][47] ] Nevertheless, a fact that was overlooked in their studies is that the LA functions as a pump, too, and similar to any other contractile pumps requires synchronized contractions to produce an optimal output.…”
Section: Whereas Many Researchers Have Considered Acts and Liaemdmentioning
confidence: 99%
See 2 more Smart Citations
“…to be predictors of the occurrence or recurrence of AF, [9][10][11][12][13][14][15][16][17] some other investigators have regarded them as early markers of LA structural remodeling. [44][45][46][47] ] Nevertheless, a fact that was overlooked in their studies is that the LA functions as a pump, too, and similar to any other contractile pumps requires synchronized contractions to produce an optimal output.…”
Section: Whereas Many Researchers Have Considered Acts and Liaemdmentioning
confidence: 99%
“…The difference between ACTs at the septal and lateral walls of the left atrium (LA) is termed the “left intra‐atrial electromechanical delay” (LIAEMD), which is a better marker of AF perpetuation from a theoretical perspective and is slightly more complex to measure than are ACTs . LIAEMD is a marker of LA dyssynchrony in the inducibility of AF in electrophysiological study, in patients with paroxysmal supraventricular tachycardias, in patients with a history of AF, and in the recurrence of AF following pulmonary vein isolation …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study by Salah et al ( 15 ) provides a further and important step in the prediction of AF recurrence after PV isolation. Previously, Evranos et al ( 16 ) used LA electromechanical delay with a cut-off value of 29.5 ms as a predictor of AF recurrence after AF ablation.…”
mentioning
confidence: 93%
“…Further, a LA dyssynchrony time of 25 ms had a positive predictive value of 53% and negative predictive value of 85.5% with the best combination of sensitivity and specificity (74% and 63%, respectively). Salah et al ( 15 ) also identified LA dyssynchrony time (HR per ms: 1.69, p<0.001) as an independent predictor of AF recurrence, and if it was ≥25 ms, then patients were prone to AF recurrences during follow-up. P wave duration (PWD) for whole patient group (n=160) was 109.4±15.6 ms; the no recurrence subgroup (n=110) had a shorter PWD (103.2±13.7 ms).…”
mentioning
confidence: 98%